Surgical Treatment of Rhinogenic Contact Point Headache: An Experience from a Tertiary Care Hospital - Peric,Aleksandar (2016)
Abstract Introduction Even in the absence of inflammatory disease, facial pain often results from pressure of two opposing nasal mucosa surfaces. Objectives The objective of this study is to assess the efficacy of surgical treatment of contact point headache. Methods Our study enrolled patients with unilateral facial pain and without nasal/ paranasal sinus disease. We confirmed the presence of mucosal contact by nasal endoscopy and by computed tomography. Forty-two subjects with the three most common anatomical variations underwent complete evaluation: 17 with concha bullosa (CB), 11 with septal deviation (SD), and 14 with septal spur (SS). All participants were treated by topical corticosteroid, adrenomimetic, and antihistamine. The patients without improvement were treated surgically. We assessed the severity of pain using a Visual Analogue Score (VAS) before surgical treatment and one, six, twelve, and twenty-four months after. Results The patients with SS had more severe facial pain in comparison with patients with CB (p=0.049) and SD (p=0.000). The subjects with CB had higher degree of facial pain than the ones with SD (p=0.001). After an unsuccessful medical treatment and surgical removal of mucosal contacts, the decrease of headache severity was more intense in patients with CB and SS (p=0.000) than in the patients with SD (p=0.01). Conclusion Our results suggest that topical medications have no effects and that surgical removal of mucosal contacts could be effective in the treatment of contact point headache. The results of surgical treatment were better in cases of facial pain caused by SS and CB, than in those caused by SD.